Why Does Digital Learning Matter? Digital Competencies, Social Justice and Critical Pedagogy in Initial Teacher Education - Helen Coker (University of Windsor, 2020)
Digital tools and spaces are becoming prevalent in schools across the world requiring the development of digital skillsets for student-teachers. Digital technology, in enabling education to extend beyond the space and time boundaries of the conventional classroom (Seifert, T., Sheppard, B. Wakeham, M., 2015) , brings the digital landscape into the classroom and firmly into the frame of reference for those preparing student-teachers to enter the profession. For Initial Teacher Education (ITE) programmes which foreground social justice, the digital (technology which is linked to the internet) goes far beyond a skillset or a discrete subject. Engaging with digital learning encompasses the 21st century context - both local and global - in which student-teachers and their future pupils are situated. Developing a critical pedagogic approach involves understanding the context in which one lives and enabling learners to challenge or change it (Freire, 1996) . For those working in ITE a postdigital lens provides a means to understand the context in which they are situated. Critical pedagogy enables student-teachers to understand that context and challenge the inequities which persist, preparing them not simply to navigate the digital landscape, but to engage with it critically. Reflecting on student-teacher learning this article explores the digital dimension, highlighting the importance of digital learning when engaging with critical pedagogy and social justice in ITE.